The Use of Digital Heritage in the Construction of Virtual Exhibitions - Grzunov, Laura; Lučić, Tonči; Valovičić, Marta (Bobcatsss, 2023)
Cultural heritage is the testimony of time, space and society and the identification card of the people and nation. GLAM institutions are in charge of storing, preserving and protecting cultural heritage, as well as enabling its use. Šošić (2014, p. 833) states that cultural heritage represents the totality of creations or phenomena in the material and spiritual life of every nation and humanity. Digitization has changed the way material is accessed as well as the way material is communicated. Also, digitalization has provided access to materials that are of significant importance to the culture of the entire community. The development of technology has certainly enabled various forms of access to collections in GLAM institutions, and digitization has provided easier access to materials. Seiter-Šverko (2012, p. 2) emphasizes that digitalization also enables the presentation of cultural heritage to a wider circle of users. From the above, it can be concluded that technology and digitalization are increasingly affecting the management and visibility of information institutions. Today, virtual exhibitions are considered as one of the creative forms of digitalization, intended for the presentation of cultural heritage. Virtual exhibitions are used in information institutions to make valuable collections visible to end users (Foo, Leng, Hoe-Lian & Cheong, 2009). They can also contribute to a more effective presentation of the cultural aspect of the institution and the community. The focus of this paper is on the use of digital heritage in the construction of a virtual exhibition. A case study method will be used. The research will describe the creation of a virtual exhibition, In the footsteps of Glagolitics from Ugljan and Pašman, made as part of the university project Digitization, bibliographic description, and research of texts written on Glagolitic, Croatian Cyrillic and Latin scripts until the end of 19th century in Zadar and Šibenik area (further in text: Written Heritage). The aim of the case study that will be applied to this research is to explore - the possibilities of creating a virtual exhibition with the help of two tools and to compare the effectiveness of these two tools in communicating digital heritage. Also, the paper will explore the positive effects and benefits of the application of new technologies, more precisely virtual exhibitions in education, culture, tourism and other areas. The tools that will be used to create the virtual exhibition, and on the basis of which the comparative analysis will be done, are StoryMap KnightLab and SpaceTime Layers. Digitized content produced within the Written Heritage project will be used to create a virtual exhibition. The virtual exhibition will include materials and catalog descriptions from the Written Heritage catalogue, photographs taken in the field as part of the project In the Footsteps of Glagolitics from Ugljan and Pašman. Based on theoretical assumptions and the implementation of a case study, the paper will try to answer two research questions: 1. What are the benefits of communication of digital heritage through virtual exhibitions? 2. For what purposes can virtual exhibitions be used?